Catheter Ablation in AF - Nichols, Emma Hitt (MD Conference Express, 2014)
The underlying mechanisms of atrial fibrillation (AF) and its initiation are not well understood, yet catheter ablation can effectively terminate AF in many patients. This article discusses the benefits of ablation for patients with AF.